The Implementation and Development of Multiculturalism-Based Scouting Education in Junior High School - Sofwan, Sofwan; Rachman, Maman; Samsudi, Samsudi (Universitas Negeri Semarang, 2016)
Scouting Education helps the students toachieve competence in cognitive, psychomotor, and affective domains. The statements of the problemin this study are: 1) how is the scouting education management model that has been held in the Junior High School? 2) howis the development of the management model of multiculturalism-based scouting education according to the needs? 3) how is the model of multiculturalism-based scouting educationin SMP developed? This study aims at: 1) describing the management model of scouting education in Junior High School, 2) developing a management model of multiculturalism-based scouting education in Junior High School,3) producing a viable and valid management model of multiculturalism-based scouting education in the Junior High School. This research employed Research and Development (R & D). The focus of research was the development of management model of multiculturalism-based scouting education in Junior High School. The data was collected through interview, observation, documentation, and Focus Group Discussion (FGD). The data measurement used theoretical and empirical validities. The validity of the data used the construct validity, triangulation of sources, methods, internal, and external. Based on the preliminary research, three public schools that became the subject of research were SMP 1 Mranggen, SMP 3 Mranggen, and SMP 2 Demak. Those state SMPs have had the vision and mission, but have not possessed any multicultural education subject. The existing scouting management has not been reflected in the planning, organizing, implementing, and monitoring (POAC).